INTEGRATING RISK MAPS IN THE DEFINITION OF MUNICIPAL TERRITORIAL MODELS - Mileu, Nelson (2018)
The integration of risk mapping into land use options at the municipal level is an issue of recognized importance as a risk mitigation strategy. This article seeks to know how risk is integrated in territorial spatial planning models and how it can help the development of a decision support system. For this purpose, a set of interviews were carried out with in some portuguese municipalities, who considered in the documentary elements of the master plan any type of risk mapping. The results of the interviews were submitted to a qualitative analysis, based on the computer-assisted analytical approach known as "NCT", or "Noticing things", "Collecting things" and "Thinking about things". The results of the analysis indicate that the hazards/risks incorporated in territorial spatial planning models depend fundamentally on the legal obligations and are integrated in an individual way and only with the classes of higher hazard/susceptibility. This result is a demonstration that in spatial planning models there is no integration with the various dimensions of the vulnerability. Regarding the situation diagnosed, the integration of the hazard component with vulnerability could be one of the development axes to be addressed in the implementation of a spatial decision support system to support spatial planning.